Comparison of Cormack Lehane grading system and intubation difficulty score in patients intubated by D-blade video and direct Macintosh laryngoscope: a randomized controlled study - Iva Pažur; Branka Maldini; Vedran Hostić; Ognjen Ožegić; Melanija Obraz (Acta Clinica Croatica, 2016)
D-blade is a relatively new device in the field of videolaryngoscopy, designed for airway management by enabling indirectoscopic glottic view. In our study, we investigated efficiency of D-blade in comparison with direct Macintosh laryngoscope (gold standard). Fifty-two adult patients with normal airway scheduled for elective surgery in general anesthesia were randomly assigned in D-blade video or direct Macintosh group. In the first video group, patients were laryngoscoped and intubated by D-blade, and in the second group laryngoscopy and intubation were performed by Macintosh laryngoscope. Glottic view was evaluated according to Cormack Lehane grading system (C-L), while duration of intubation and easiness of intubation were evaluated according to the intubation difficulty score (IDS). Additionally, hemodynamic parameters were recorded before and after induction. There were no statistically significant between-group differences in time to intubation, easiness of endotracheal tube insertion, C-L, and IDS. In comparison with direct Macintosh laryngoscope, D-blade showed similar but still favorable characteristics. In our opinion, D-blade is a useful device in airway management and should be used in daily anesthesiologist work.